Arab Spring-Arab Fall Divergent Transitions in post-2011 Tunisia and Egypt. - Erdogan, Ayfer (Lexington Books, 2021)
The Arab Spring was born in Tunisia and collapsed in Egypt. What did Tunisia do right and Egypt so wrong? This book analyzes the political, economic and constitutional developments in Tunisia and Egypt before and after the Arab uprisings and seeks to answer why their transitional paths diverged substantially.